2015
DOI: 10.3390/antiox4040662
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Antioxidant Activity of the Extracts of Eugenia uniflora Leaves. Characterization of the Anti-Inflammatory Properties of Aqueous Extract on Diabetes Expression in an Experimental Model of Spontaneous Type 1 Diabetes (NOD Mice)

Abstract: Medical and folklore reports suggest that Eugenia uniflora (E. uniflora) is a functional food that contains numerous compounds in its composition, with anti-inflammatory, antioxidant and anti-diabetic effects. In the present study, we investigated the best solvents (water, ethanol and methanol/acetone) for extracting bioactive compounds of E. uniflora leaves, assessing total phenols and the antioxidant activity of the extracts by 2,2-Diphenyl-1-picrylhydrazyl (DPPH), Ferric Reducing Antioxidant Power (FRAP), 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 45 publications
0
22
1
6
Order By: Relevance
“…To limit oxidative damage, the body produces antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). Additionally, substances acquired through diet, such as flavonoids, vitamins, and minerals, form an important defense barrier [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…To limit oxidative damage, the body produces antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). Additionally, substances acquired through diet, such as flavonoids, vitamins, and minerals, form an important defense barrier [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Encontram-se, na literatura, estudos que reportam efeitos antidiarreico (Almeida et al, 1995), antidiabético (Arai et al, 1999), antimicrobiano Biasi-Garbin et al, 2016), antioxidante (Sobral-Souza et al, 2014;Schumacher et al, 2015), hepatoprotetor (Victoria et al, 2013), antinociceptivo e hipotérmico (Amorim et al, 2009), anti-Trypanosoma cruzi (Santos et al, 2012;Azeredo et al, 2014) e antiLeishmania (Rodrigues et al, 2013) para as folhas de E. uniflora.…”
Section: Introductionunclassified
“…Examples are glutathione peroxidase, catalase and superoxide dismutase while exogenous anti-oxidants are derived from our diet, such as flavonoids, vitamins A, C and E, polyphenols, Phenolic acid, carotenes 13 . Schumacher et al 14 reported that the treatment of type-1-diabetes mellitus in non-obese diabetic (NOD) mice with aqueous extracts of E. uniflora leaf reduce the risk for diabetes as a result of the high antioxidant activity of the extract. Hepatic glutathione and serum insulin levels can be preserved and reduction in serum lipid peroxidation can be obtained in NOD mice, if treated with aqueous extract of E. uniflora leaf 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Schumacher et al 14 reported that the treatment of type-1-diabetes mellitus in non-obese diabetic (NOD) mice with aqueous extracts of E. uniflora leaf reduce the risk for diabetes as a result of the high antioxidant activity of the extract. Hepatic glutathione and serum insulin levels can be preserved and reduction in serum lipid peroxidation can be obtained in NOD mice, if treated with aqueous extract of E. uniflora leaf 14 . The industrial relevance of the leaves of E. uniflora has been proposed by the antimicrobial properties exhibited by the essential oil extracted from its leaves 15 .…”
Section: Introductionmentioning
confidence: 99%